Effect of hypertriglyceridemia on left ventricular global longitudinal strain in patients with coronary heart disease in Jilin Province, China: a cross-sectional study - Na, Lin; Cui, Wenjing; Li, Xinqi; Chang, Jing; Xue, Xin (Frontiers in Cardiovascular Medicine, 2023)
Abstract Aims: Using speckle tracking technology to investigate the effect of hypertriglyceridemia on the global longitudinal strain(GLS) of the left ventricle in patients with coronary heart disease in the early stage, and to explore the value of myocardial strain in early identification of cardiac dysfunction in patients with coronary heart disease in the pre-heart failure stage. Methods: A cross-sectional study of 138 participants was conducted in Jilin Province, China. Basic clinical, biochemical, and echocardiographic data were obtained for all patients. Myocardial strain parameters were compared between the hypertriglyceridemia and normal triglyceride level groups and the effect of hypertriglyceridemia on early left ventricular global longitudinal strain impairment in coronary heart disease patients was evaluated. Results: The overall longitudinal strain of the left ventricle was smaller in the hypertriglyceridemia group than in the normal triglyceride group. After the multivariate Logistic regression model adjusting for the influence of confounding factors, the results remained stable. Conclusions: The risk of impairment of global longitudinal strain of the left ventricle in patients with coronary heart disease is positively correlated with triglyceride levels, and hypertriglyceridemia maybe an independent risk factor affecting early cardiac dysfunction in the pre-heart failure stage of patients with coronary heart disease.